1999
DOI: 10.1097/00007890-199910150-00028
|View full text |Cite
|
Sign up to set email alerts
|

PREVENTION OF DE NOVO HEPATITIS B INFECTION IN RECIPIENTS OF HEPATIC ALLOGRAFTS FROM ANTI-HBc POSITIVE DONORS

Abstract: Combination therapy with HBIG and lamivudine may prevent de novo HBV infection in anti-HBs-, HbsAg- recipients of hepatic allografts from anti-HBc+ donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
160
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 12 publications
2
160
1
1
Order By: Relevance
“…[31][32][33] Previous studies have recommended that the patients who receive anti-HBc-positive organs should undergo a minimum of one year of lamivudine or HBIg prophylaxis, regardless of their own HBV status, because their grafts harbor HBV and can cause disease in the transplant recipient. 10,[13][14][15] The disadvantages of HBIg in combination with lamivudine are exceedingly high cost, inconvenient usage, possible mercury intoxication in some preparations, and the emergence of a resistant mutant virus. 16,17,34,35 However, there are uncertain conclusions regarding the prophylactic management after transplantation in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Previous studies have recommended that the patients who receive anti-HBc-positive organs should undergo a minimum of one year of lamivudine or HBIg prophylaxis, regardless of their own HBV status, because their grafts harbor HBV and can cause disease in the transplant recipient. 10,[13][14][15] The disadvantages of HBIg in combination with lamivudine are exceedingly high cost, inconvenient usage, possible mercury intoxication in some preparations, and the emergence of a resistant mutant virus. 16,17,34,35 However, there are uncertain conclusions regarding the prophylactic management after transplantation in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies have suggested that lamivudine, a nucleoside analog that inhibits HBV replication, can be used in addition to or as an alternative to HBIg in such cases. [13][14][15] However, this prophylactic treatment is very expensive and has been associated with the emergence of a resistant HBV strain, because of a specific mutation in the HBV-RNA-dependent DNA polymerase at the tyrosine-methionine-aspartate-aspartate locus. 16,17 The more precise definition of HBV infection is the identification of HBV-DNA in the serum or tissue of the suspected viral host.…”
Section: E Novo Hepatitis B Virus (Hbv) After Orthotopicmentioning
confidence: 99%
“…4,5 There have been documented instances of de novo occurrence of hepatitis B (HBV) infection in recipients of these organs. 3,5,[6][7][8][9][10][11] The reported rates of de novo HBV in HBcAb-negative recipients receiving an HBcAb-positive donor liver vary from 30% [6][7][8] to up to 80% 3,9,20 when no antiviral prophylaxis is used after surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Progressive liver disease can develop in these patients. 2,5,9 Antibody to HBsAg (antiHBs) ϩ transplant recipients have the lowest risk for developing de novo HBV infection from an anti-HBc ϩ liver allograft.…”
mentioning
confidence: 99%
“…Recipients positive only for anti-HBc have an intermediate risk (13%), and those negative for both anti-HBc and anti-HBs have the greatest risk (72%) for de novo infection. 3,4 Hepatitis B immunoglobulin (HBIG) is routinely administered to prevent the recurrence of HBV infection in HBV-infected liver transplant recipients. Two studies using an HBIG-based regimen successfully prevented de novo HBV infection in recipients of antiHBc ϩ allografts.…”
mentioning
confidence: 99%